Inconsistent findings for the eyes closed effect in children: the implications for interviewing child witnesses - Kyriakidou, Marilena; Blades, Mark; Carroll, Dan (Frontiers in Psychology, 2014)
A child who alleges that they have been the victim of a crime will be interviewed by police officers. During a police interview it is important that the interviewer obtains the most accurate testimony possible from the child. Previous studies have shown that if children have their eyes closed during an interview they sometimes report more correct information. This paper includes two studies. In Experiment 1 156 children experienced an event and were then questioned about it. Half the children answered with their eyes open and half with their eyes closed. The participants with eyes closed provided more correct information. In Experiment 2 152 children answered questions in different conditions including eyes open and eyes closed conditions. In contrast to Experiment 1 there was no beneficial effect for the eyes closed condition. These inconsistent results are discussed with reference to actual police interviews. It is suggested that until there has been more research into eyes closed procedures caution should be taken in recommending such procedures for police interviews with children.